A half-century of studies of growth hormone insensitivity/Laron syndrome: A historical perspective. (June 2016) - Rosenbloom, Arlan L.
Abstract: A growth hormone (GH) dependent substance responsible for sulfate uptake by costal cartilage of hypophysectomized rats, labeled sulfation factor, was reported in 1957. In 1962 the radioimmunoassay for GH was described. The clinical picture of severe GH deficiency but with high serum concentrations of GH was reported in 3 siblings in 1966 and followed by a 1968 report of 22 patients belonging to 14 consanguineous oriental Jewish families in Israel. Defective sulfation factor generation was demonstrated in 15 of these individuals and in a 1971 report; FFA response to IV GH and growth response to GH injections suggested competitive saturation of peripheral tissue receptors by an abnormal GH. However, studies published in 1973 demonstrated normal fractionation of their circulating GH, and normal binding of GH from 22 patients to various antisera used for radioimmunoassay. In 1976, the Israeli investigators reported that circulating GH from 7 patients reacted normally in the recently developed radioreceptor assay for GH. In 1984, using hepatic microsome pellets, they demonstrated that the defect was a failure of GH binding to receptors. Characterization of the human GH receptor (GHR) gene, reported in 1989, included the initial description of a genetic defect of the GHR in 2 of 9 Israeli patients. At about the same time began the identification in Ecuador of what was to become the largest population of GH insensitivity in the world, ~ 100 individuals, and the only substantial population with a common mutation of the GH receptor. Treatment studies with recombinant IGF-I began in 1990. Growth response was modest compared to that of GH treated GH deficient subjects. The spectrum of GH insensitivity has expanded beyond GH receptor deficiency to include postreceptor abnormalities: IGF-I gene mutation (1996); IGF-I receptor mutation (2003); signal transducer and activator of transcription 5b mutation (2003); and mutation of the GH-dependent acid labile subunit (2004). Conclusion: Rare conditions of GH insensitivity caused by GH receptor and postreceptor abnormalities have provided insights into the processes of growth, body composition, and metabolism. Highlights: Identifying GH insensitivity (1966) depended on development of radioimmunoassay for GH in 1962. Recognizing that defect was in GH receptor took nearly 20 years. Large population in Ecuador discovered (1989) comprising 1/3 of all cases. Treatment with recombinant IGF-I begun in 1990. Spectrum of GHI expanded with IGF-I gene and receptor, STAT5b, and ALS mutations.